Respiratory motion artifacts during arterial phase imaging with gadoxetic acid: Can the injection protocol minimize this drawback?. Issue 4 (9th February 2017) - Polanec, Stephan H.; Bickel, Hubert; Baltzer, Pascal A.T.; Thurner, Patrick; Gittler, Florian; Hodge, Jacqueline C.; Bashir, Mustafa R.; Ba‐Ssalamah, Ahmed
Abstract : Purpose: To determine which of three gadoxetic acid injection techniques best reduced the contrast‐related arterial‐phase motion artifacts. Materials and Methods: This Institutional Review Board (IRB)‐approved, retrospective study included a cohort of 78 consecutive patients who each had serial gadoxetic acid‐enhanced 3.0T magnetic resonance imaging (MRI) of the liver (0.025 mmol/kg body weight) performed with at least two of three injection techniques: M1 test bolus, undiluted, power‐injected 1 mL/s; M2 test bolus, diluted 50% with saline, power‐injected 1 mL/s; M3 fixed delay, undiluted, manually injected. Blinded to the injection method, three readers independently rated the randomized images for arterial‐phase motion artifacts, arterial‐phase timing, and arterial‐phase lesion visibility using a four‐point Likert scale. Results: Regarding respiratory artifacts, gadoxetic acid arterial‐phase images were judged better with M3 (2.7 ± 0.7) and were significantly less than those with M1 (2.1 ± 1.1) ( P  = 0.0001). Arterial‐phase M2 (2.50 ± 0.89) images were rated significantly better than arterial‐phase M1 images ( P  = 0.012), but the difference between arterial‐phase images with M3 and M2 scores was not statistically significant ( P  = 0.49). Arterial‐phase timing was significantly better for M1 compared to M3, and for M2 compared to M3 ( P < 0.0001 for both). The area under the curve was 0.59–0.68. However, there was no significant difference between M1 and M2 ( P  = 0.35). With regard to arterial‐phase lesion visibility, there was no significant difference in the ratings between any of the three injection techniques ( P  = 0.29–0.72). Interreader agreement was moderate to substantial (κ = 0.41–0.62). Conclusion: A diluted, power‐injected protocol (M2) seems to provide good timing and minimize artifacts compared with two other injection methods. No significant difference was found in lesion visibility between these three methods. Level of Evidence: 3 Technical Efficacy: Stage 1 J. Magn. Reson. Imaging 2017;46:1107–1114.